2010
DOI: 10.1007/s00394-010-0103-1
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin addition improves human neutrophils function: in vitro study

Abstract: Taken together our results are supportive to a beneficial effect of astaxanthin-treatment on human neutrophils function as demonstrated by increased phagocytic and fungicide capacity as well as by the reduced superoxide anion and hydrogen peroxide production, however, without affecting neutrophils capacity to kill C. albicans. This process appears to be mediated by calcium released from intracellular storages as well as nitric oxide production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 45 publications
3
43
0
4
Order By: Relevance
“…ASTA addition significantly improves phagocytic capacity of neutrophils treated with glucose and FFA. A similar result was obtained by our group previously [30]. Long-chain FFA and some of their derivatives and metabolites can modify intracellular production of reactive oxygen species (ROS), in particular superoxide and H 2 O 2 .…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…ASTA addition significantly improves phagocytic capacity of neutrophils treated with glucose and FFA. A similar result was obtained by our group previously [30]. Long-chain FFA and some of their derivatives and metabolites can modify intracellular production of reactive oxygen species (ROS), in particular superoxide and H 2 O 2 .…”
Section: Discussionsupporting
confidence: 79%
“…Many authors have reported that astaxanthin has a greater affinity with hydrogen peroxide when compared to superoxide [27][28][29]. Recently, Macedo et al [30] showed that astaxanthin significantly reduced the production of pro-inflammatory cytokines, such as tumor necrosis factor-α and interleukin-6 in lipopolysaccharide-stimulated neutrophils. The authors also showed that astaxanthin improved neutrophil phagocytic and microbicidal capacity and reduced superoxide anion and hydrogen peroxide production, which appeared to be mediated by calcium released from intracellular storages and nitric oxide production.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It was suggested that astaxanthin was potentially nutritional therapeutic agent for prevention/prophylaxy of immune-impaired diseases, such as type 2 diabetes, sepsis, and cardiovascular disorders [35]. Macedo et al [36] showed that astaxanthin significantly reduced the production of pro-inflammatory cytokines, such as tumor necrosis factor-a and interleukin-6 in lipopolysaccharidestimulated neutrophils. The results also showed that astaxanthin improved neutrophil phagocytic and microbicidal capacity and reduced superoxide anion and hydrogen peroxide production, which appeared to be mediated by calcium released from intracellular storages and nitric oxide production, indicating a beneficial effect of astaxanthin on human neutrophils function [36].…”
Section: Anti-inflammatory Effectsmentioning
confidence: 99%
“…Astaxanthin was found to reduce induced swelling of rat paw, that vitamin E did not reduce 28 . Macedo et al 66 showed that astaxanthin significantly reduced the production of pro-inflammatory cytokines, such as tumor necrosis factor-a and interleukin-6 in lipopolysaccharide stimulated neutrophils.…”
Section: Astaxanthin and Inflammationmentioning
confidence: 99%